To determine the diagnostic accuracy of magnetic resonance imaging in detecting rectal cancer, keeping histopathology as a gold standard. - Naz, Nasreen; Azmatullah, Uzma; Ali, Afaque; Majid; Ahmed , Adeel (International Journal of Endorsing Health Science Research, 2021)
Background: Magnetic Resonance Imaging (MRI) has a premier role in detecting rectal cancer and is considered superior for diagnosing tumour recurrences. It is the modality of choice by which patients with total abdominal perineal (AP) resection can be fully evaluated. This study aimed to evaluate the diagnostic accuracy of MRI in the detection of rectal carcinoma in suspected cases, keeping histopathology as a gold standard. Methodology: A descriptive cross-sectional study was conducted in the radiology department of Dow University of Health Sciences, Civil Hospital, Karachi, from 19th May to 18th November 2018. A total of 181 patients with a history of bleeding per rectum, altered bowel habits and abdominal pain were included. High-resolution 2D T2-weighted fast spin-echo sequences in the sagittal, axial and coronal planes were taken. Patients were followed for histopathology reports. The diagnostic accuracy of MRI for rectal carcinoma was calculated in terms of diagnostic accuracy, sensitivity, specificity, using histopathology as a gold standard. Results: There were 63% male and 37% female patients. The mean symptoms duration was 60.61 ± 7.18 weeks. 64.1% were presented with bleeding per rectum, 52.5% with altered bowel habits and 31.5% with abdominal pain. 35.4% of cases were diagnosed positive by MRI, and 43.6% cases through histopathology. Sensitivity, Specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy were 85.9%, 79.5%, 69.6%, 91.2%, and 81.76% respectively. Conclusion: It was concluded that MRI has 85.9% sensitivity, 79.5% specificity, and 81.76% diagnostic accuracy in detecting rectal cancers proving its reliability in detecting both early and recurrent rectal cancers.